The potential causes of myasthenia and fasciculations in severely ill ME/CFS patients: the role of disturbed electrophysiology - Wirth, Klaus J.; Steinacker, Jürgen M. (Frontiers in Physiology, 2026)
Patients with severe myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) are bedridden and suffer from hypersensitivities to light and noise, severe orthostatic intolerance reducing cerebral blood flow, and skeletal muscle symptoms, including loss of force, fatigue, pain, fasciculations, and cramps. Because neurological investigations exclude neuronal causes of myasthenia, we hypothesize a muscular pathomechanism. In previous articles, we considered insufficient activity of the Na+/K+-ATPase to be the main cause of mitochondrial damage via high intracellular sodium that reverses the transport mode of the sodium-calcium-exchanger to import calcium, causing calcium overload. Low Na+/K+-ATPase activity also causes sarcolemmal depolarization, leading to less effective action potential propagation and loss of force. Depolarization brings the membrane potential closer to the threshold potential, causing hyperexcitability that explains fasciculations and cramps. These increase sodium influx during excitation to further increase the workload of Na+/K+-ATPase. Thereby, depolarization causes further depolarization. Higher intracellular sodium favors calcium overload and mitochondrial damage, which lowers the energy supply of Na+/K+-ATPase and increases the reactive oxygen species, further inhibiting Na+/K+-ATPase. The muscle is in a state of depolarization even at rest. Depolarization and mitochondrial damage reinforce each other. Thus, dysfunction of Na+/K+-ATPase as a single mechanism can explain the different skeletal muscle symptoms of severely ill ME/CFS patients, comprising loss of force, fatigue, and fasciculations.